Human CLP1 mutations alter tRNA biogenesis, affecting both peripheral and central nervous system function. - Karaca, Ender; Weitzer, Stefan; Pehlivan, Davut; Shiraishi, Hiroshi; Gogakos, Tasos; Hanada, Toshikatsu; Jhangiani, Shalini N; Wiszniewski, Wojciech; Withers, Marjorie; Campbell, Ian M; Erdin, Serkan; Isikay, Sedat; et al. (Cell, 2014)
CLP1 is a RNA kinase involved in tRNA splicing. Recently, CLP1 kinase-dead mice were shown to display a neuromuscular disorder with loss of motor neurons and muscle paralysis. Human genome analyses now identified a CLP1 homozygous missense mutation (p.R140H) in five unrelated families, leading to a loss of CLP1 interaction with the tRNA splicing endonuclease (TSEN) complex, largely reduced pre-tRNA cleavage activity, and accumulation of linear tRNA introns. The affected individuals develop severe motor-sensory defects, cortical dysgenesis, and microcephaly. Mice carrying kinase-dead CLP1 also displayed microcephaly and reduced cortical brain volume due to the enhanced cell death of neuronal progenitors that is associated with reduced numbers of cortical neurons. Our data elucidate a neurological syndrome defined by CLP1 mutations that impair tRNA splicing. Reduction of a founder mutation to homozygosity illustrates the importance of rare variations in disease and supports the clan genomics hypothesis.
Keywords: Abnormalities, Multiple; Animals; Central Nervous System Diseases; Cerebrum; Child, Preschool; Endoribonucleases; Female; Fibroblasts; Humans; Infant; Male; Mice; Mice, Inbred CBA; Microcephaly; Mutation, Missense; Nuclear Proteins; Peripheral Nervous System Diseases; Phosphotransferases; RNA, Transfer; Transcription Factors